Effects of radiation, curvature, and preferential diffusion on the extinction of laminar non-premixed flames - Yushan Gao; Wang Han; Zheng Chen; Qingfei Fu; Lijun Yang (AIP Advances, 2022)
The combined effects of radiative heat loss, curvature, and preferential diffusion on laminar non-premixed flames (or flamelets) are investigated in this work by using asymptotic analysis. A general theoretical description of flame temperature and extinction is derived for curved flames with non-unity Lewis numbers and radiative heat loss. Special attention is paid to the effects of curvature and radiative heat loss on the flammability limits. The results show that (1) a curved flamelet always has two extinction limits: one is the kinetic extinction limit, and the other is the curvature-induced extinction limit for the adiabatic case or the radiative extinction limit for the radiative case; (2) the curvature exerts a different influence on the adiabatic and radiative flames. Specifically for the adiabatic flame, it is found that both flame temperature and flame position significantly decrease as the curvature increases and that a new extinction limit at a low stretch rate occurs due to the existence of curvature. Furthermore, a higher curvature coupled with the increase in the Lewis number results in a lower flammability limit and narrower flammable zone. Therefore, the presence of curvature has a negative impact on the adiabatic flame. On the contrary, for the radiative flame, the results show that the increase in curvature has a positive effect on the flammability limit and thereby increases the flammable zone. It is expected that curved flamelets hold smaller (larger) flammable zones than planar flamelets under the adiabatic (radiative) condition. All results show that the change in flame curvature has a stronger effect on the flame structure and extinction than the deviation of the Lewis number from unity.